On G-strucures in gauge/string duality. - Jerome Gaillard (2011)
We study how G-structures can be used in the framework of gauge/string duality. The reason why such concept is so powerful is that C-structures are a very natural way of describing supersymmetry in a geometric setting. We investigate more specifically two different points. First, we are interested in how G'-structures can help with constructing and understanding supergravity backgrounds with sources that can be interpreted as flavours in the dual field theory. In particular, we show that the smearing procedure, for flavouring a background, is expressed more clearly when described in terms of G-structures. We discuss this problem in general terms, before applying the newly developed techniques to several examples, some already known and some new. We see that the way one adds and distributes branes in a supersymmetric background is strongly constrained by the preservation of supersymmetry. We then also look at how one can develop solution-generating techniques from Cr-structures, that derive complex solutions out of simple ones, by tinning on new fluxes. We specialise to the two cases of SU(3) and G2-structures. In both examples, we use the solution-generating methods on known solutions to create new, previously unknown solutions. We show that those techniques can be applied to flavoured as well as unflavoured backgrounds.